Differential equations with applications to mathematical physics - Ames, William F.; Harrell, Evans M.; Herod, J. V., 1937- (Mathematics in science and engineering ;, 1993)
Contributors from North America, Europe and Japan present articles at the forefront of research in differential equational and mathematical physics. Topics covered include nonlinear differential and integral equations, semiclassical quantum mechanics and spectral and scattering theory.